Microsurgical Anatomy of the Lateral Condylar Vein and Its Clinical Significance. Issue 1 (24th September 2014) - Matsushima, Ken; Funaki, Takeshi; Komune, Noritaka; Kiyosue, Hiro; Kawashima, Masatou; Rhoton, Albert L
Abstract: BACKGROUND: Although the lateral condylar vein has been encountered in some skull base approaches and used as a route to access the anterior condylar venous confluence, few descriptions can be found in the literature regarding its morphology. OBJECTIVE: To examine the anatomy of the lateral condylar vein and its clinical significance. METHODS: The craniocervical junctions of 3 cadaveric heads, 15 dry bones, and 25 computed tomography venography images were examined. RESULTS: The lateral condylar vein was identified in 88.0% of paracondylar areas, with an average diameter of 3.6 mm. This vein originated near the jugular bulb, descended along the lateral surface of the occipital condyle and medial to the internal jugular vein, cranial nerves IX to XI, and rectus capitis lateralis muscle to drain into the vertebral venous plexus surrounding the vertebral artery. The veins were classified according to their origin from either (1) the anterior condylar confluence or (2) the internal jugular vein. In some specimens, the lateral condylar vein courses within a small osseous canal lateral to the occipital condyle, the paracondylar canal, which was identified in 16.7% of paracondylar areas in the dry bones. CONCLUSION: The lateral condylar vein may be encountered in exposing the jugular bulb, hypoglossal canal, or foramen magnum. This vein has been reported to be a main draining route of dural arteriovenous fistulas, in which case it can be utilized as a transvenous route for endovascular treatment, or obliterated. An understanding of the anatomy of this vein may prove useful in planning skull base and endovascular procedures.